(3QSGdI aj GdJhMjOs - (3GdcGTj Ch GdcGTGfj, ceGd GdOjf, YHO GdQRGb Hf CMeO GHf CHj GdZfGFe, J(B730(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi NjQ Ndbg eMeO(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B3(3,U(B350s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds